2018
DOI: 10.1016/j.coal.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic and Raman spectroscopic characterization of coal from Himalayan fold-thrust belts of Sikkim, India

Abstract: The present study focuses on the investigation of the optical anisotropy, optical sign, textural heterogeneity and deformational features of the maceral grains along with the Raman spectral characteristics of the seven coal samples collected from the Himalayan fold-thrust belts of Sikkim State, India. The coal samples were extremely fragile and pulverized due to the intense tectonic deformation. The maceral composition revealed the dominance of semifusinite over collotelinite grains. The calculated maximum vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…The data from Bonoldi et al (2016) deviate from trend because they used additional bands (1693 and 1547 cm ‐1 ) in the G‐band region from sedimentary samples, altering the G‐band width significantly as discussed by Lupoi et al (2017). The discrepancy of the data from Ghosh et al (2018) in the range Rmax 5.94–8.66% is explained by the very high laser power of 18 mW or their option to suppress the additional D2‐band for deconvolution, which leads to larger G‐band width. Data from Kelemen and Fang (2001) diverge possibly due to laser power and/or fitting procedures.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The data from Bonoldi et al (2016) deviate from trend because they used additional bands (1693 and 1547 cm ‐1 ) in the G‐band region from sedimentary samples, altering the G‐band width significantly as discussed by Lupoi et al (2017). The discrepancy of the data from Ghosh et al (2018) in the range Rmax 5.94–8.66% is explained by the very high laser power of 18 mW or their option to suppress the additional D2‐band for deconvolution, which leads to larger G‐band width. Data from Kelemen and Fang (2001) diverge possibly due to laser power and/or fitting procedures.…”
Section: Resultsmentioning
confidence: 88%
“…The authors who studied OM/CM by Raman spectroscopy and reported the G‐band width along with vitrinite reflectance are: Ammar and Rouzaud (2012); Bonoldi et al (2016); Ghosh et al (2018); Guedes et al (2010); Henry et al (2018, 2019b); Hinrichs et al (2014); Jubb et al (2018); Kelemen and Fang (2001); Kwiecinska et al (2010); Li et al (2019); Lupoi et al (2017); Quirico et al (2005); Rantitsch et al (2004, 2016a); Schmidt et al (2017); Spötl et al (1998); and Wilkins et al (2014). The acquisition protocols of all authors are described in Table in supporting information, the full raw data sets are available at Table in supporting information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CG3300, CG3301, and CG3302 samples were picked up from the Jorethang area and CG3303 was collected near Namchi at the south Sikkim. Sample CG3304 was sampled from the north of the Kamling village (Ghosh et al 2018(Ghosh et al , 2020. Furthermore, CG3305 and CG3306 were collected near the Reshi Khola in the Reshi town (Ghosh et al 2018(Ghosh et al , 2020.…”
Section: Samplingmentioning
confidence: 99%
“…For instance, fluids migrating through brecciated coals in fault zones probably lead to cleat mineralization and elemental enrichment [58,59,61]. Specifically, the concentrations of Ti, Sc, Ta, U and rare earth elements all increase as the coal deformation increases, while the concentration of Mo decreases with increasing deformation intensity, which can be mainly ascribed to the coal dynamic metamorphism accompanied by frictional thermal effects [62][63][64][65]. Analogously, concentrations of rare earth elements in fault-related boreholes are higher than those in unrelated boreholes in specific coal seams.…”
Section: Introductionmentioning
confidence: 99%